2007
DOI: 10.1029/2006rs003540
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation measurements using VHF wind profiler radars: Measuring rainfall and vertical air velocities using only observations with a VHF radar

Abstract: [1] In addition to a proper radar calibration, quantitative estimation of precipitation from radars also requires the extraction of the precipitation signal out of the Doppler spectra. It also requires the proper conversion of this precipitation signal into reflectivity factor. This study shows how the measurement of rainfall and vertical air velocities can be performed using only observations from a radar operating at the VHF band (i.e., meter wavelengths). We verify the assumption that the dielectric factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 23 publications
(44 reference statements)
0
20
0
Order By: Relevance
“…The carrier frequency of MUR is 46.5 MHz so that it is mainly sensitive to clear air refractive index fluctuations at half the radar wavelength in size (i.e. the Bragg scale), even in presence of clouds or weak precipitations (less than 4 mm h −1 according to Campos et al, 2007). Therefore, small-scale refractivity turbulence can be monitored by MUR in both clear air and cloudy conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The carrier frequency of MUR is 46.5 MHz so that it is mainly sensitive to clear air refractive index fluctuations at half the radar wavelength in size (i.e. the Bragg scale), even in presence of clouds or weak precipitations (less than 4 mm h −1 according to Campos et al, 2007). Therefore, small-scale refractivity turbulence can be monitored by MUR in both clear air and cloudy conditions.…”
Section: Resultsmentioning
confidence: 99%
“…It is necessary to exclude periods of convective rain that may be present in the datasets from any DSD retrievals. It should be noted that this limitation is not present when using VHF wind profilers (Campos et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…If the clear-air contribution is known, it can be removed from the Doppler spectrum prior to retrieving DSDs. Several methods for isolating and removing the clearair contribution have been explored, including the use of multiple radar frequencies such as UHF and VHF (Schafer et al 2002;Rajopadhyaya et al 1999), cluster analysis , deconvolution (Rajopadhyaya et al 1993;Lucas et al 2004), fitting model spectra to observed spectra (Wakasugi et al 1986;Kobayashi and Adachi 2005), and using measurements from a single VHF wind profiler to quantify both precipitation signals and the ambient air velocity (Campos et al 2007). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard forms for this equation assume, most of the time, an average scatterer cross section per unit volume (or radar reflectivity) that is constant within the sampling volume of a given range gate. Under these conditions and neglecting the effect of the convolution of the transmitted pulse with the reflectivity profile, the radar equation is given by the following expression [for details on its derivation, see Campos et al (2007); Eq. (18)]:…”
Section: Introductionmentioning
confidence: 99%